Can concurrent teaching promote equal biomechanical adaptations at front crawl and backstroke swimming? - Costa, Mário Jorge (2017)
The biomechanical adaptations in front crawl and backstroke swimming, as influenced by the implementation of a concurrent teaching programme were analysed. Sixteen participants (19.75 ± 1.13 years) underwent a 30 weeks intervention characterized by an increasing complexity to accomplish motor skills in the following order: (i) lower limbs propulsion; (ii) lower limbs propulsion synchronized with breathing cycle; (iii) lower limbs propulsion synchronized with one upper limb action; (iv) lower limbs propulsion synchronized with both breathing cycle and one upper limb action; (v) full swimming stroke; (vi) motor trajectory of the arms stroke. Performance and biomechanics were measured at front crawl and backstroke during three time points throughout the programme. There were improvements in performance over time at front crawl (21.49 s to 19.99 s, p<0.01) and backstroke (27.15 s to 24.60 s, p = 0.01). Significant improvements were found for velocity at front crawl (1.13 m/s to 1.22 m/s, p<0.01) and backstroke (0.92 m/s to 1.00 m/s, p<0.01). Stroke frequency increased at backstroke (0.64 to 0.73 Hz, p = 0.01), while the intra-cyclic variation of the velocity decreased at front crawl (0.13 to 0.12%, p = 0.02). There was also a moderate-high inter-subject variability in response to the programme. These findings prove that a programme of 30 weeks teaching concurrently front crawl and backstroke is effective to promote similar biomechanical adaptations in low-tier swimmers. However, each subject shows an individual response to better adapt the biomechanical actions and to reach a higher level of expertise.